Sociodemographic, Clinical and Genetic Correlates of Aggressive and Auto-Aggressive Behaviour in Alcohol-Dependent Individuals – Preliminary Study - Czarnecki D; Holec EA; Chodkiewicz J; Ziółkowski M; Gorzkiewicz M (Psychology Research and Behavior Management)
Damian Czarnecki,1 Elżbieta Anna Holec,2 Jan Chodkiewicz,3 Marcin Ziółkowski,1 Marta Gorzkiewicz4 1Department of Preventive Nursing, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Torun, Torun, Poland; 2Department of Nursing, Stanisław Staszic State University of Applied Scences in Piła, Pila, Poland; 3Institute of Psychology, Department of Clinical Psychology and Psychopathology, University of Łodz, Łodz, Poland; 4Department of Molecular Genetics and Justice, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Torun, Torun, PolandCorrespondence: Damian Czarnecki, Department of Preventive Nursing, Nicolaus Copernicus University in Torun, Collegium Medicum in Bydgoszcz, ul. Ignacego Łukasiewicza 1, Bydgoszcz, 85-821, Poland, Tel +48 52  585 42 82, Email czarneckidamian@cm.umk.plPurpose: Reducing the risk of aggressive behaviour requires preventive measures that depend on our knowledge of predisposing factors. The study’s aim was to compare sociodemographic variables, clinical variables and the frequency of gene polymorphisms predisposing to destructive behaviour between subpopulations of individuals with a history of suicidality and/or of aggression, both being treated for alcohol dependence.Patients and Methods: Sixty-nine patients hospitalised for alcohol dependence participated in the study. The sociodemographic, clinical (SADD, BPAQ) and genetic variables were compared between subpopulations of alcohol-dependent patients selected according to type of aggressive behaviour, including a history of suicidal behaviour and control nonalcohol-dependent group. Polymorphisms of MAOA, COMT, DRD2 and DAT1 loci that are known as risk factors of mental dysfunctions were investigated.Results: The subpopulation of patients with suicide attempts had a longer time in education than patients with aggressive and suicidal behaviour (11.9 vs 9.7 years). Patients with suicide attempts and patients with aggression had lower levels of alcohol dependence than patients with comorbid suicide attempts and concomitant aggression. For the MAOA gene lower frequency of the G/G genotype with tendency to statistical significance was observed among patients burdened by suicidal behaviour in comparison to patients with aggression and a significantly higher A/G genotype compared to cases with aggression and controls. In the case of COMT polymorphism, the G/G genotype was reported significantly less often among patients with suicide attempts and comorbid aggression than among patients with control group).Conclusion: Compared to patients with either only suicidal tendencies or aggression, those with comorbid aggression and suicide attempts are characterised by poorer social performance. Genetic variation in MAOA loci may be a risk factor for impulsive behaviour like suicidal behaviour, and especially aggression.Keywords: gene polymorphisms, aggression, suicide behaviour, alcohol-dependence